Pengaruh Persepsi Harga, Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Pelanggan di Jw Marriott Hotel Jakarta - Adela, Antika; Prawoto (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
The purpose of this research is to determine the influence of price perceptions, product quality and service quality of JW Marriott Hotel Jakarta on customer satisfaction, by applying quantitative methods and Accidental Sampling at JW Marriott Hotel Jakarta. The research results show a value of 0.874 with a significance of 0.384. With a significance of more than 0.05, HO is accepted, indicating that price perception has no partial effect on customer satisfaction at JW Marriott Hotel Jakarta. Product quality with a calculated t value of 3.108 and a significance of 0.002. This states that product quality also partially influences customer satisfaction at JW Marriott Hotel Jakarta. The t-count service quality results produce a value of 6.704 with a significance of 0.000. With a significance of less than 0.05, HO is rejected, which means that service quality has a partial effect on customer satisfaction.